PENGARUH KECERDASAN EMOSIONAL TERHADAP KEPUASAN KERJA DAN STRES KERJA PADA THE SEMINYAK BEACH RESORT AND SPA - Nuraningsih, Ni Luh Putu; Surya Putra, Made (E-Jurnal Manajemen, 2015)
The purpose of this study was to determine the effect of emotional intelligence on job satisfaction and job stress at The Seminyak Beach Resort and SPA. Samples from this study amounted to 148 people. The sampling method used was probability sampling is simple random sampling. Data analysis techniques used in this research is path analysis. The analysis showed that emotional intelligence has positive influence on job satisfaction, job satisfaction negatively affect job stress, emotional intelligence negatively affect job stress.
Keywords: emotional intelligence, job satisfaction, job stress